Salvia officinalis induces antidepressant-like effect, anxiolytic activity and learning improvement in hippocampal lesioned and intact adult rats - El Gabbas, Zineb; Bezza, Kenza; Laadraoui, Jawad; Makbal, Rachida; Aboufatima, Rachida; Chait, abderrahman (Bangladesh Journal of Pharmacology, 2018)
The anxiolytic and antidepressant like effects of Salvia officinalis extract (50, 100 and 200 mg/kg) were evaluated using marble burying, forced swimming and open-field tests in intact and hippocampal lesioned rats. Additionally, S. officinalis was evaluated on rat's memory using conditioned learning test. and we screened the methanolic extract for anti-oxidant activity, phytochemical and high performance liquid chromatography analyses. The administration of sage extract showed a significant reduction of immobility time in lesioned and intact animals during the forced swim test and anxiolytic effect in marble burying test. In the case of conditioned learning paradigm, memory enhancement was observed in sage treated group which indicates a cognition improvement. These activities seem to be related to the anti-oxidant capacity and the phytochemicals (phenolic, flavonoid, and tannin) detected into the extract of S. officinalis. The findings show that the methanolic extract of sage possess antidepressant-like effect, anxiolytic activity and also may contain bioactive compounds that stimulate learning in rat.